Pelatihan Dan Pendampingan Penyusunan Laporan Keuangan Yayasan Masjid Agung Gamping - Sukirno, Sukirno; Setyorini, Dhyah; Adhi Nugroho, Mahendra; Tiara Novitasari, Budi; Wahyu Dewanti, Patriani (Universitas Pahlawan Tuanku Tambusai, 2023)
Financial reporting is a form of accountability and a critical component to maintaining transparency and accountability, and provides financial information as a basis for decision-making, building donor trust, assessing performance, and managing fundamental risks. The Gamping Great Mosque Foundation is a non-profit organization established to improve the governance of the Gamping Great Mosque to be more trustworthy, professional, and accountable. The condition of financial management at the Gamping Great Mosque Foundation, which has not been standardized is one of the obstacles in disclosing the foundation's financial statements. The purpose of the service activity is to provide knowledge and insight into preparing the Mosque's financial statements to the Gamping Great Mosque Foundation administrators in managing and reporting the foundation's finances. Service activities are carried out using lectures, training, discussion, and mentoring methods during the service period by involving the management and support staff of the Gamping Great Mosque Foundation. Service activities run according to the planned stages. However, the service team experienced obstacles with limited human resources to manage and report the finances of the Gamping Great Mosque Foundation. Keywords: Financial Reporting; Mentoring; Gamping Great Mosque Foundation